Optimalisasi Wawasan tentang Media Sosial & E-commerce Sebagai Strategi Unggulan dalam Branding UMKM di Desa Bicak - Anisa Putri Maharani; Putri Kurnia Sari; Iola Riris Simanjuntak; M. Arief Safi'i; Syarief Hidayat (CV. ALIM'SPUBLISHING, 2024)
Bicak Village is a village with promising economic potential, especially through the Micro, Small and Medium Enterprises (MSME) sector. However, challenges in marketing and branding local products are still a significant obstacle for MSMEs in this village. This article aims to optimize the use of social media and e-commerce as superior branding strategies to increase the competitiveness of MSMEs in Bicak Village. The method used in this article focuses more on a qualitative analysis approach, namely data collection, observation, and direct interviews with MSME actors. The results found are exploring how MSME actors can utilize digital platforms to increase product visibility, reach a wider market, and strengthen their image. brand. The research results show that implementing this digital strategy will not only increase sales, but will also have a positive impact on the sustainability of MSME businesses in Bicak Village.